A hybrid of Kansei engineering (KE) and analytical hierarchy process (AHP) to develop conceptual designs of portable oil spill skimmer - Abdullah, Lokman; Ramanathan, Rprakash; Md Fauadi, Muhammad Hafidz Fazli; Syed Mohamed, Muhammad Syafiq; Kamaludin, Khairun Najmi (IIUM Press, 2023)
Currently, there are huge demands on developing a design that fulfils the characteristics of performance, cost, safety, and aesthetics. However, the conceptual design stages in industrial products lack the involvement of user requirements as it is typically focused on the product's performance.Consequently, specific criteria such as the product's ease of use, safety,and robustness cannot be compared and measured when designing industrial products. Owing to this reason, this research proposes a new technique that integrates Kansei Engineering with Analytical Hierarchy Process(AHP) to address the issue. The research objective is to investigate an oil spill skimmer's user and technical requirements by incorporating the Kansei Engineering method. The approach to carry out this research is to incorporate the Kansei and the basic AHP methods.Kansei Engineering will suggest the required design elements that must be included to design and fabricate a portable oil spill skimmer. At the same time,the AHP method is used to select the best design based on the developed conceptual design.The effectiveness of the proposed method was verified by comparing it with other established methods,such as TOPSIS (Technique of Order Preference by Similarity to Ideal Solution).Moreover, sensitivity analysis was used to investigate the robustness of the AHP result.There are 5 conceptual designs in total, assessed in this research. The result showed that out of the 5 conceptual designs, design number 3 has the highest ranking (priority ranking = 0.2603). Thus, the most suitable conceptual design for the portable oil spill skimmer to be fabricated is design 3. The finding also shows that the result from AHP was valid and robust.